Evaluasi Penggunaan Supporting Applications For Quick Data Search (SuApQuDaS) Dengan Metode PIECES Framework - Yana Iqbal Maulana; Agus Salim (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
The SuApQuDaS application was built to meet the needs of a team in one of the bureaus in managing data, especially the data search process to improve service to customers. Evaluation is a planned activity to assess a problem that occurs using instruments and the results can be compared with benchmarks to obtain conclusions so that solutions can be found to solve problems that arise. Meanwhile, information system evaluation can be carried out in different ways and at different levels, depending on the purpose of the evaluation. Its purpose is to assess technical capabilities, operational implementation, and system utilization. To simplify the evaluation, an analysis method is offered with the PIECES framework which describes the 6 focus of weakness analysis, namely Performance, Information and Data, Economy, Control and Security, Efficiency and Service. Based on the analysis method of the PIECES framework in measuring the level of evaluation, the value of each domain is obtained, namely the performance domain gets a score of 4.09, the domain information and data gets a score of 4.18, the domain economics gets a score of 4.18, the domain control and security gets a score 4.11, domain efficiency gets a score of 4.17, and domain service gets a score of 4.13.